THE EFFECT OF HEALTH EDUCATION ON THE PREVENTION OF DENGUE HEMORRHAGIC FEVER ON THE KNOWLEDGE AND SKILLS OF POSYANDU CADRES IN TANJUNGREJO VILLAGE, JANTI HEALTH CENTER WORKING AREA, MALANG CITY - Amanah, Mei Tantri Nur; Sangkot, Hartaty Sarma; Lundy, Fiashriel; Rachman, Moh Zainol (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
DHF is a health problem that is commonly found and even results in death. Prevention efforts are carried out by providing education using videos. DHF cases in Tanjungrejo Village in 2023 were 16 people. The purpose of the study was to determine the effect of health education on the prevention of dengue hemorrhagic fever on the knowledge and skills of posyandu cadres of Tanjungrejo Village, Janti Health Center Working Area, Malang. This study applied quantitative methods with a pre experiment design in the form of one group pre-test post-test. Data collection techniques with puposive sampling according to inclusion and exclusion criteria as many as 40 samples. Data collection instruments used questionnaires and observation sheets. Data were analyzed univariately to obtain a description of the characteristics of respondents, and a description of the independent and dependent variables. Bivariate analysis applied the Wilcoxon Signed Ranks test. The results showed that there were changes in knowledge and skills before and after video education. The mean value of knowledge before education 6.35 increased to 9.83 the difference was 3.48. The average value of skills before education 6.15 increased to 9.75 the difference was 3.6. The conclusion of this study is that health education with video media is able to make the knowledge and skills of posyandu cadres increase about dengue prevention in Tanjungrejo Village, Janti Health Center Working Area, Malang.